Current State of the Diagnosis of Invasive Pulmonary Aspergillosis in Lung Transplantation - Herrera, Sabina; Husain, Shahid (Frontiers in Microbiology, 2019)
As the number of lung transplants performed worldwide each year continues to grow, the success of this procedure is threatened by the incidence of non-CMV infections such as invasive aspergillosis. Despite tremendous efforts and the availability of numerous diagnostic tests (especially in hematological malignancies) the diagnosis of invasive aspergillosis continues to be a challenge. Lung transplantation remains a unique clinical scenario, where additional host defences are immunocompromised, making many of the available tests unsuitable. In this review we will navigate through the myriad of diagnostic tests currently available and how they apply to this unique patient population, as well as have a look into what the future holds.